Karakteristik Perilaku Manajemen Perawatan Diri Hipertensi pada Lansia di Daerah Rural - Irwina Angelia Silvanasari; Nurul Maurida; Trisna Vitaliati; Achmad Ali Basri (Nursing Sciences Journal, 2023)
Proper control, especially in the self-care management of hypertension in the elderly, is reported to be able to prevent unwanted complications. The aim of this research is to identify the characteristics of hypertension self-care management behavior in the elderly. The type of research was descriptive with a sample size of 150 out of 240 elderly people with hypertension in rural areas. The variable studied was hypertension self-care management behavior. The research instrument is the HSBMQ questionnaire. Data analysis is in the form of univariate analysis in the form of frequency distribution of the indicators of the variables studied. The research results showed that elderly people with hypertension had adequate behavior in self-care management for hypertension. This indicates that elderly people with hypertension are quite good in terms of self-integration, self-regulation, interaction with health workers, monitoring blood pressure, and compliance with treatment. Elderly people with hypertension should be able to increase their implementation of a healthy lifestyle such as diet and physical activity, be able to properly recognize the signs of hypertension and appropriate actions to overcome them, be able to discuss with health workers regarding action plans to overcome the hypertension they suffer from, be able to monitor blood pressure regularly , and able to comply with recommended treatment.